2003
DOI: 10.4049/jimmunol.171.2.1061
|View full text |Cite
|
Sign up to set email alerts
|

TRAIL-R2 (DR5) Mediates Apoptosis of Synovial Fibroblasts in Rheumatoid Arthritis

Abstract: TRAIL has been proposed as an anti-inflammatory cytokine in animal models of rheumatoid arthritis (RA). Using two agonistic mAbs specific for TRAIL-R1 (DR4) and TRAIL-R2 (DR5), we examined the expression and function of these death receptors in RA synovial fibroblast cells. The synovial tissues and primary synovial fibroblast cells isolated from patients with RA, but not those isolated from patients with osteoarthritis, selectively expressed high levels of cell surface DR5 and were highly susceptible to anti-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
81
0
2

Year Published

2004
2004
2007
2007

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 104 publications
(89 citation statements)
references
References 33 publications
6
81
0
2
Order By: Relevance
“…This is consistent with previously reported results by Ichikawa et al, who additionally showed that an anti-DR5 mAb prevents erosive arthritis in a murine xenograft model for human RA (8). Importantly, the anti-DR5 antibody developed by Ichikawa et al does not seem to be hepatotoxic (8,12) and is therefore a good substitute for soluble TRAIL therapy, which induces apoptosis in normal human hepatocytes (11).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…This is consistent with previously reported results by Ichikawa et al, who additionally showed that an anti-DR5 mAb prevents erosive arthritis in a murine xenograft model for human RA (8). Importantly, the anti-DR5 antibody developed by Ichikawa et al does not seem to be hepatotoxic (8,12) and is therefore a good substitute for soluble TRAIL therapy, which induces apoptosis in normal human hepatocytes (11).…”
Section: Discussionsupporting
confidence: 90%
“…OPG, which is 1 of the 5 known TRAIL receptors, inhibits osteoclastogenesis by binding to RANK ligand and increases bone density in vivo (18). Soluble TRAIL has been described to block the antiosteoclastogenic activity of OPG in vitro (7); this suggests that administration of soluble TRAIL has the potential to accelerate osteoporosis in RA patients (8).…”
Section: Expression Of Trail-r2 On Ra Synovial Fluid Fibroblastsmentioning
confidence: 99%
See 3 more Smart Citations